ANALISIS KERUSAKAN PADA TURBIN DENGAN METODE VIBRATION ANALYSIS - Situmorang, Egi Seven; Suryadi, Dedi; Alparisi, Ahmad Salman (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2023)
In the operation of the turbine, various problems can occur which cause damage, one of which is caused by vibration. Vibration analysis is one of the supporting factors to minimize excessive vibrations in the turbine. Predictive maintenance activities in the form of conditional monitoring vibration or vibration monitoring of actual conditions are carried out to determine the symptoms of damage to the turbine. Measurements were carried out using VibeXpert II based on ISO 18016-5 standards with operating conditions of 70 MW turbine load and 500RPM rotation measured on the DE Turbine and NDE Generator. The highest value is in the horizontal DE Turbine 77.04 µm (pk-pk) and 104 µm (pk-pk) on the NDE Generator. This value is already in the acceptable zone to operate in the long term. The results of spectrum analysis that can be identified as the cause of the vibrations that occur are indications of unbalance on the DE Turbine and Overhung on the NDE Generator.